Soluble Aβ1-42 suppresses TNF-α and activates NLRP3 inflammasome in THP-1 macrophages. (November 2018) - Gupta, Mehak; Wani, Abubakar; Ul Ahsan, Aitizaz; Chopra, Mani; Vishwakarma, Ram A; Singh, Gurdarshan; Kumar, Ajay
Highlights: Soluble amyloid beta (sAβ1-42 ) plays a dual role in the process of inflammation. sAβ1-42 activates NLRP3 inflammasome on the one hand and suppresses the secretion of TNF-α on the other hand. sAβ1-42 may have protective role in the brain against inflammatory damage. Abstract: Deposition of amyloid-β in Alzheimer's disease is accompanied by chronic inflammation, which involves raised levels of pro-inflammatory cytokines TNF-α, IL-6 and IL-1β. However, the role of Aβ1 -42 in the inflammatory process, before it gets deposited into aggregates has not been investigated thoroughly. Through this study, we are illustrating the dual role of soluble Aβ1 -42 (sAβ1-42 ) in activating the NLRP3 inflammasome and simultaneously inhibiting TNF-α secretion. Our data suggested that the treatment of chronically induced THP-1 macrophages and N9 microglial cells with sAβ1 -42 can suppress the major inflammatory cytokine TNF-α without affecting the level of IL-6. However, the activation of NLRP3 inflammasome was well evidenced by secretion of IL-1β, increased expression of NLRP3 and caspase-1, implicating sAβ1 -42 in enhancing and suppressing one or other type of inflammation. Further investigation revealed that sAβ1 -42 was able to severely abrogate the expression of NF-κB, p50 and restricting the translocation of NF-κB, p65 to nucleus by inhibiting phosphorylation of IκB-α in THP-1 macrophages. These data indicate that the sAβ1 -42 may play a dual role during inflammatory process, wherein, it may be involved in protecting the cells from inflammatory damage due to TNF-α. This ability of sAβ1 -42 might be playing some role in protecting the brain cells during the process of aging and Alzheimer's disease, where, chronic inflammatory environment plays a vital role.